2019
DOI: 10.36963/ijtst.19060101
|View full text |Cite
|
Sign up to set email alerts
|

Numerical simulation of convective heat transport within the nanofluid filled vertical tube of plain and uneven side walls

Abstract: Two-dimensional transient natural convective flow in a vertical tube of plain and uneven side-walls containing cobalt-kerosene nanofluids is analyzed using a nonhomogeneous dynamic model. The vertical right wall of the enclosure is maintained at a constant low temperature and the left wall is heated by a uniform thermal condition whereas the horizontal side-walls are insulated. The Brownian motion and thermophoretic phenomena of the nanoparticles are considered in the model. The governing nonlinear momentum, e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…In a recent study, Uddin et al (2019) have identified the unit anomaly of the last term of equation (11) and revised this model as follows: where D T is the thermophoresis coefficient (ms −2 ) and DTl is a dimensionless quantity equal to DT.…”
Section: Formulation Of the Problemmentioning
confidence: 99%
“…In a recent study, Uddin et al (2019) have identified the unit anomaly of the last term of equation (11) and revised this model as follows: where D T is the thermophoresis coefficient (ms −2 ) and DTl is a dimensionless quantity equal to DT.…”
Section: Formulation Of the Problemmentioning
confidence: 99%
“…Balamurugan et al [21] exposed an influence of radiation absorption, viscous and joules dissipation on mhd free convection chemically reactive and radiative flow in a moving inclined porous plate with temperature dependent heat source. Uddin et al [22] reported on numerical simulation of convective heat transport within the nanofluid filled vertical tube of plain and uneven side walls. Severno and Campo [23] studied a finite strip method applied to steady heat conduction and thermal radiation in a planar slab: absorbing ̶ emitting gray material and parallel diffuse surfaces.…”
Section: B0mentioning
confidence: 99%
“…5 Computational Procedures Using Galerkin weighted residual brand of finite element method (FEM), the dimensionless governing Eqs. (22)(23)(24)(25)(26) with the boundary conditions (27)(28)(29)(30)(31) are simulated numerically. Well description of this method can be found in the books and papers by Uddin et al [28], Zienkiewicz et al [41], Zienkiewicz et al [42], Codina [43], Uddin [44], Rahman et al [45] and Al Kalbani et al [46].…”
Section: The Average Nusselt Numbermentioning
confidence: 99%
“…Due to the potential applications of nanofluid in different fields of science and engineering such as solar energy, chemical, microchannel, bioengineering and automotive, it has received considerable attention by many researchers like Alsabery et al [23,24], Al Kalbani et al [25], Uddin et al [26][27][28], Astanina et al [29], Sathiyamoorthy et al [30], Mehryan et al [31] and Rahman et al [32] who have studied the dynamics of nanofluids in various cavities. Mathematical modelling of nanofluids provides a representation of the parameters governing the problem that can be examined with the least possible cost, and thereby provide a good understanding of the situation.…”
Section: Introductionmentioning
confidence: 99%